Mutations in TSPEAR, Encoding a Regulator of Notch Signaling, Affect Tooth and Hair Follicle Morphogenesis. - Alon Peled; Ofer Sarig; Liat Samuelov; Marta Bertolini; Limor Ziv; Daphna Weissglas-Volkov; Marina Eskin-Schwartz; Christopher A Adase; Natalia Malchin; Ron Bochner; Gilad Fainberg; Ilan Goldberg; et al. (PLoS Genetics)
Despite recent advances in our understanding of the pathogenesis of ectodermal dysplasias (EDs), the molecular basis of many of these disorders remains unknown. In the present study, we aimed at elucidating the genetic basis of a new form of ED featuring facial dysmorphism, scalp hypotrichosis and hypodontia. Using whole exome sequencing, we identified 2 frameshift and 2 missense mutations in TSPEAR segregating with the disease phenotype in 3 families. TSPEAR encodes the thrombospondin-type laminin G domain and EAR repeats (TSPEAR) protein, whose function is poorly understood. TSPEAR knock-down resulted in altered expression of genes known to be regulated by NOTCH and to be involved in murine hair and tooth development. Pathway analysis confirmed that down-regulation of TSPEAR in keratinocytes is likely to affect Notch signaling. Accordingly, using a luciferase-based reporter assay, we showed that TSPEAR knock-down is associated with decreased Notch signaling. In addition, NOTCH1 protein expression was reduced in patient scalp skin. Moreover, TSPEAR silencing in mouse hair follicle organ cultures was found to induce apoptosis in follicular epithelial cells, resulting in decreased hair bulb diameter. Collectively, these observations indicate that TSPEAR plays a critical, previously unrecognized role in human tooth and hair follicle morphogenesis through regulation of the Notch signaling pathway.